Assessment of the Upstream Churia Hills and Downstream Terai Plains Linkage: An Environmental Services Perspective - Singh, BK (Banko Janakari, 2010)
The Terai, considered the granary of Nepal, is facing serious threat from siltation originating from the Churia hills mainly due to heavy deforestation together with forest and watershed degradation. Discussions with local community people revealed that no such problem existed 5-6 decades ago when the Churia forest was intact. All the forestry sector policies had recognized the Churia hills as fragile and environmentally sensitive, but the concerned government agencies and the local community people have not been able to conserve this region effectively. There is heavy exploitation of the Churia hills for the extraction of timber, firewood, non-timber forest products, and for grazing resources. In addition, gravel, sand and boulders are also being extracted for the sake of revenue to the local governments. Jalad River of Dhanusha district originating from the Churia hills has been converting fertile and productive agriculture lands into barren river beds at the rate of 25 hectares a year. The Churia hills should be conserved for the environmental services of the watershed to the entire Terai region rather than for provisioning tangible forest products services only to the upstream local communities. Key Words: Environmental services; Churia-Terai linkage; PES; upstream-downstream DOI: 10.3126/banko.v20i1.3504 Banko Janakari, Vol. 20, No. 1 pp.17-23